Influence of respiration on variability of peak systolic blood flow velocity in common carotid artery: preliminary study - Utsunomiya, Yoshiki; Azhim, Azran; Suzuki, Asato; Akutagawa, Masatake; Emoto, Takahiro; Yoshizaki, Kazuo; Obara, Shigeru; Tanaka, Hiroyuki; Kinouchi, Yohsuke (Springer Berlin Heidelberg, 2009)
The purpose of this study is to investigate the influence of respiration on variability of peak systolic velocity (PSV) in common carotid artery (CCA). There were significant correlation between peak systolic velocities and its RR intervals that evaluated from synchronized measurement of electrocardiogram (ECG) and Doppler blood velocity. Heart rate variability (HRV) was typically used to assess autonomic nervous activity in physiology. We studied the influence of breathing frequency component on power spectra in PSV for three healthy subjects. A respiratory belt sensing device, an ECG monitor and a developed blood velocimeter were used to evaluate breathing patterns (BP), HRVs and PSVs, simultaneously.